Electrochemical Investigation of Thiobacillus Denitrificans in a Bacterial Composite. Issue 13 (15th October 2020) - Abada, Bachira; Boumerfeg, Sabah; Haddad, Ahmed; Etienne, Mathieu
Abstract : The use of biocathodes in bioelectrochemical systems (BES) for the removal of nitrate from waste water has become a vital field for research. However, the elucidation of the underlying extracellular electron transfer (EET) fundamentals of denitrifying biocathodes is rarely done, but it is required for a deeper BES understanding and engineering. This study shows the thermodynamics of microbial electron transfer for reduction of nitrate and nitrite using bacteria immobilized on a biofilm used in BES. Thiobacillus denetrificans are best species that demonstrate both direct extracellular electron transfer and the phenomenon of microbial denitrification. The Cyclic voltammetry and chronoamperometry confirm the reduction of the nitrate at a potential of −0.46 V and the nitrite at −0.68 V vs Ag/AgCl, however the electrochemical response changes according to both the concentration and the temperature.